(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
The features and advantages of innovative structural and technological solutions in construction based on lightweight metal structures are discussed there in the article. The problems of energy- and resource-saving in Ukraine are revealed. Investigations of the main energy problems of Ukrainian cities are presented through the example of Odessa. The spacial layout and structural features of the cottage estate project in Leski village are also described here. The necessity of applying the methodology of factor evaluation in the optimization of structural and technological solutions of cottage building frame assembly is substantiated taking into consideration the energy efficiency. There are also presented the results of optimization of structural and technological solutions. Theку are specified two main factors affecting the choice of architectural, structural and technological solutions for the frame assembly: quantitative and qualitative. Qualitative criteria include: the possibility of year-round installation; ecological compatibility; fire safety. Quantitative criteria include: cost of construction; minimum wall thickness (excluding insulation); frost resistance; sound insulation; duration of construction; operational life; coefficient of thermal conductivity. In the process of selecting alternatives and determining criteria, the communicative individual method is used - when decision options are generated by a single expert. Based on the data of factors evaluation, on a 5-point scale, the Light steel thin-walled structures technology scored the highest number of points - 67 points, the smallest - silicate brick - 37 points; it is evidence that solution of the Light steel thin-walled structures shows the best performance. There are proposed some ways for solving the downsides of the Light steel thin-walled structures, such as the formation of thermal bridges, which can be reduced in two ways: by using of double frames or external heat insulation systems; ensuring the building tightness in relation to the wind, to the air and to the steam migration through the structure by the obligatory installation of wind protection and a vapor barrier; increasing the fire resistance limit of the Light steel thin-walled structures is provided in one of the ways: spraying and painting with various fire-resistant materials; plasterboard cladding; plastering.